2012
DOI: 10.2147/ijn.s30699
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intratumoral administration on biodistribution of 64Cu-labeled nanoshells

Abstract: Background: Gold nanoshells are excellent agents for photothermal ablation cancer therapy and are currently under clinical trial for solid tumors. Previous studies showed that passive delivery of gold nanoshells through intravenous administration resulted in limited tumor accumulation, which represents a major challenge for this therapy. In this report, the impact of direct intratumoral administration on the pharmacokinetics and biodistribution of the nanoshells was systematically investigated. Methods: The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 45 publications
3
44
0
1
Order By: Relevance
“…5), likely due to its poor tumor retention. Similar results were reported by Xie et al for intratumorally injected nontargeted 64 Cu-labeled gold nanoshells, which were retained in head and neck squamous cell carcinoma xenografts in nude rats, whereas 64 Cu-DOTA or 64 Cu-DOTA-PEG not linked to the gold nanoshells were cleared from these tumors over 44 h (25). Liver and spleen uptake remains a major challenge to the use of systemically administered AuNP for cancer treatment (26), but this obstacle was overcome using intratumorally injected 177 Lu-T-AuNP and 177 Lu-NT-AuNP.…”
Section: Discussionsupporting
confidence: 88%
“…5), likely due to its poor tumor retention. Similar results were reported by Xie et al for intratumorally injected nontargeted 64 Cu-labeled gold nanoshells, which were retained in head and neck squamous cell carcinoma xenografts in nude rats, whereas 64 Cu-DOTA or 64 Cu-DOTA-PEG not linked to the gold nanoshells were cleared from these tumors over 44 h (25). Liver and spleen uptake remains a major challenge to the use of systemically administered AuNP for cancer treatment (26), but this obstacle was overcome using intratumorally injected 177 Lu-T-AuNP and 177 Lu-NT-AuNP.…”
Section: Discussionsupporting
confidence: 88%
“…An hour before laser irradiation, the animals were injected intratumorally with the solution of gold nanorods in the amount of 30% of the tumor volume. The injection of the gold nanoparticles directly into the tumor was conducted according to the paper of Xie and co-workers, 24 where the authors demonstrated that using such a modi¯cation of intratumoral injection leads to prolonged retention of nanoparticles in tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…An hour before laser irradiation, the animals were injected intratumorally by the solution of the gold nanorods in the amount of 30 % of the tumor volume. The injection of the gold nanoparticles directly into the tumor was conducted according to the paper by Xie and co-workers [18], where the authors demonstrated that using such modification of intratumoral injection leads to prolonged retention of nanoparticles in tumor tissue. The animals were irradiated with an 808-nm CW laser LS-2-N-808-10000 (Laser Systems, Ltd., St. Petersburg, Russia) at a power density …”
Section: In Vivo Experimentsmentioning
confidence: 99%